Evaluation of Estonian innovation system - Hannu Hernesniemi (The Research Institute of the Finnish Economy (ETLA), 2000)
In this report the Estonian national innovation system (NIS) and especially the effectiveness of technology policy and the functioning of policy organisations is evaluated. The national innovation system is a set of institutions, which jointly and individually contribute to the development and diffusion of new technologies and provide the framework for the technology policy of a nation. Estonian research and technology development (RTD) investments are very low in international comparison. RTD expenditure is only 0.5 percent of GDP. This is one quarter of that of the European Union and OECD countries. In particular, there is a lack of private technology development investments. Primary focus of the public investment is on basic research and on those fields of science that are not connected to industries. Anyhow Estonia has managed to attract a remarkable amount of foreign direct investment (FDI) per capita. FDIs have been important channels for technology transfer. The evaluator agrees with the National Development Plan, suggesting that RTD intensity has to rise to 1.2 per cent of GDP in the year 2002. This means around EEK 1 bill, mostly financed by state. Later RTD financing should rise to 2.2 per cent of GDP (average intensity in the OECD and EU countries in 1995) until the year 2010, with increasing private financing. The status of technology policy has to be raised, because technology development is the key factor for growth in the Estonian economy in the future. The evaluator suggests that parliament has to approve a master plan for developing and utilising new technology in Estonia. The Evaluator also proposes that a new Technology Agency with sufficient personnel, good premises and a developed network should replace the Innovation Foundation.
Keywords: 330; Estonia; Innovation system; Technology policy; Evaluation